Analisis Kemampuan Pemecahan Masalah Peserta Didik pada Materi Fluida Statis Berbantuan 3D Pageflip Professional - Elfrida Loliyanti Bura; Yustina Yesisanita Yeyen; Maria Enjelina Suban; Alfonsus Wajong (Journal on Education, 2024)
Problem solving ability is an ability that must be mastered by every student in order to be able to solve problems that are often found in every learning activity. Indicators of problem solving include being able to understand the problem, formulate a strategy or resolution plan, resolve the problem according to the plan that has been made and check the answers again. This research aims to analyze students' problem solving abilities in static fluid material assisted by 3D pageflip professional. The method used is descriptive. The research subjects were 21 students in class XI MIPA 2 SMA Negeri 1 Waigete. The instrument used in the research was a 5-question description test. The data obtained were analyzed using descriptive analysis. The research results showed that students had difficulty working on the test questions given on the indicator of checking the answers again and were categorized as low.